Analysis of Antioxidants and Flavonoid Compounds of Ethanol Extract of Starfruit Leaves (Averrhoa Bilimbi L) Using the DPPH Method - Ersalina Nidianti; Widi Agustin Wulandari; Dina Kamelia (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2026)
Starfruit (Averrhoa bilimbi L.) is not only a commonly consumed fruit but also widely used in traditional medicine. The plant has long been utilized by the community to help treat various ailments, including coughs and rectal inflammation. This study aimed to determine the total flavonoid content and antioxidant activity of ethanol extracts of starfruit leaves that had been fractionated using n-hexane.The extraction process was carried out using the maceration method with 70% ethanol, followed by fractionation with 95% n-hexane to separate active compounds from the crude extract. The total flavonoid content in the n-hexane fraction of the ethanol extract was measured using a UV-Vis spectrophotometer at a wavelength of 229-230 nm, while antioxidant activity was evaluated using the DPPH method, also measured at 515 nm. The results showed that the total flavonoid content of the n-hexane fraction of the ethanol extract was 37,3 mgQE/g extract. The antioxidant activity test yielded an IC50 value of 6.58 μg/mL, compared to a standard IC50 value of 2.45 μg/mL for vitamin C. These findings indicate that the n-hexane fraction of starfruit leaf ethanol extract possesses very strong antioxidant properties.